PELUANG DAN TANTANGAN PENGEMBANGAN LITERASI DIGITAL DALAM PEMBELAJARAN BAHASA ARAB PADA JENJANG PENDIDIKAN DASAR - Syagif, Ahmad (Prodi PGMI STIT Sunan Giri Bima, 2023)
This paper aims to elaborate on the existence and dynamics of learning Arabic at the basic education level and its relevance to the development of digital literacy. Using a literature study type research method and analytic descriptive techniques, this paper wants to describe research problems with the help of bibliographical data sourced from writings, papers, journals, and scientific articles as well as books that are relevant. Next, analyze the opportunities and challenges of developing digital literacy in learning Arabic at the basic education level. The findings obtained are that opportunities that can be targeted include wider access to language learning resources, interactive and interesting learning experiences, availability of global connectivity and language exchange, availability of digital applications for language practice, and providing an effective evaluation and feedback system. While the challenges faced are uneven access to technology, uneven technical competence of users, language barriers, limited range of focus and attention of students, digital security risks, psychological, social and health disorders.